Local Traditions, Global Lessons: Models of Religious Harmony from Cigugur Indonesia and El-Gamaliya Egypt - Rahman, Abd.; Herman, Arfian Alinda; Arhad, Muhammad; Nur, Fakhriyah; Haramain, Haramain; Musmulyadi, Musmulyadi (Jurnal Dialog, 2025)
This research examines the dynamics, dogma, and dialogue of religious harmony through a comparative case study between Cigugur Village, Indonesia, as the center of Sunda Wiwitan belief, and El-Gamaliya, Cairo, Egypt, an old city area with Islamic and Christian communities. Using a qualitative approach based on a case study design, data was collected through in-depth interviews and participatory observation of religious leaders and local communities. The results show that in Cigugur, harmony developed from civil society initiatives through informal forums such as Bajigur, interfaith social practices, and the example of religious leaders without state intervention. In El-Gamaliya, harmony is supported by wasathiyah Islamic principles, daily social interactions and collective nationalism that create harmony between Muslims and Christians. Religious dogma in both regions is inclusive, accepting local traditions and diversity, with interfaith dialogue growing organically through shamanism rather than formal forums. This research confirms that religious harmony is effective through local values, grassroots dialogue and culture-based social integration, not just the state's normative approach. The findings are relevant to policies on religious moderation, multicultural education, and managing diversity in an increasingly complex global society.